Efficacy and safety of tofacitinib therapy in Asian patients with severe alopecia areata - Ying-Xiu Dai; Chen-Pu Yeh; Chih-Chiang Chen (Wolters Kluwer Medknow Publications, 2020)
Background: Patients with severe alopecia areata (AA), including alopecia totalis (AT) and alopecia universalis (AU), are usually resistant to treatment. While tofacitinib is emerging as a promising therapy for severe AA, little is known about its efficacy and safety in Asians. Objectives: To evaluate the efficacy and safety of tofacitinib for treating severe AA. Methods: We included patients with ≥50% scalp hair loss, disease for ≥6 months, and tofacitinib therapy for ≥4 months. The efficacy, evaluated based on the percent change in severity of alopecia tool (SALT) score, and response time, defined as time from baseline to reach >50% improvement in SALT score, were assessed. Results: We included 35 patients (21 with AA, 3 with AT, and 11 with AU). There were 18 men and 17 women (median age: 39 [range: 12-68] years). After 4-24 months of treatment, 74.3% showed clinical response, with 51.4% of the patients achieving ≥50% hair regrowth. Patients with AA showed higher percent change in SALT score than patients with AT/AU (median [interquartile range]: 60.7% [0-98.2] vs. 41.1% [8.9-98.7], P = 0.047). Initial SALT score was negatively associated with the latest percent change in SALT score (P = 0.025). Duration of disease and current episode were positively associated with response time to tofacitinib (P = 0.018 and 0.026, respectively). Patients tolerated tofacitinib well without serious adverse events. Conclusion: Tofacitinib effectively promoted hair regrowth in Asian patients with severe AA. Randomized controlled trials with larger sample size are needed to confirm the long-term efficacy and safety of tofacitinib for treating severe AA.